The roles of probiotics in the gut microbiota composition and metabolic outcomes in asymptomatic post-gestational diabetes women : A randomized controlled trial - Zubaidah, Hasain; Raja Affendi, Raja Ali; Hajar Fauzan, Ahmad; Ummul Fahri, Abdul Rauf; Oon, Seok Fang; Norfilza Mohd, Mokhtar (MDPI, 2022)
Probiotics are widely used as an adjuvant therapy in various diseases. Nonetheless, it is uncertain how they affect the gut microbiota composition and metabolic and inflammatory outcomes in women who have recently experienced gestational diabetes mellitus (post-GDM). A randomized, double-blind, placebo-controlled clinical trial involving 132 asymptomatic post-GDM women was conducted to close this gap (Clinical Trial Registration: NCT05273073). The intervention (probiotics) group received a cocktail of six probiotic strains from Bifidobacterium and Lactobacillus for 12 weeks, while the placebo group received an identical sachet devoid of living microorganisms. Anthropometric measurements, biochemical analyses, and 16S rRNA gene sequencing results were evaluated pre- and post-intervention. After the 12-week intervention, the probiotics group’s fasting blood glucose level significantly decreased (mean difference −0.20 mmol/L; p = 0.0021). The HbA1c, total cholesterol, triglycerides, and high-sensitivity C-reactive protein levels were significantly different between the two groups (p < 0.05). Sequencing data also demonstrated a large rise in the Bifidobacterium adolescentis following probiotic supplementation. Our findings suggest that multi-strain probiotics are beneficial for improved metabolic and inflammatory outcomes in post-GDM women by modulating gut dysbiosis. This study emphasizes the necessity for a comprehensive strategy for postpartum treatment that includes probiotics to protect post-GDM women from developing glucose intolerance.